Proposal for qualitative and quantitative descriptors to or characterise bamboo germplasm - Generoso, Andressa; Santos, Jardel; Carvalho, Virginia; Sacoman, Nayara; Rodrigues, Rosana (Revista Ciência Agronômica, 2015)
Bamboo is a genetic resource with evident potential for use from construction until the recovery of degraded areas. Although, characterization and evaluation studies involving bamboo species are scarce and it is difficult to define a list of specific descriptors to better meet the different genres and or bamboo species. Thus, the objective of this work were propose and test the effectiveness of qualitative and quantitative descriptors for phenotypic characterization and the study of genetic diversity among six species of bamboo introduced in Brazil. Fifteen qualitative and nine quantitative descriptors were proposed and tested in clones with one year of planting. Individuals belonging to six species of bamboo (Bambusa vulgaris, Bambusa vulgaris var. vittata, Drepanostachyum falcatum, Dendrocalamus latiforus, Phyllostachys aurea var. albovariegada and Phyllostachys edulis) were characterized on the basis of vegetative descriptors, pseudopetiole, sheath, ligule, gems and culm. The genetic divergence between the clones was estimated by the methods of grouping of Tocher and UPGMA with use of average Euclidean distance and the principal component in two-dimensional plane. Qualitative and quantitative descriptors proposed were efficient to differentiate the six species studied and quantify genetic diversity. The quantitative descriptor of sheath length was the largest contributor to differentiate the species studied.